Gathering evidence during the investigation of violent disappearances - Buchenko, Dmytro (Archives of Criminology and Forensic Sciences, 2025)
The scientific understanding of the category of “circumstances of a criminal offense” is carried out within several areas of criminal law. Despite this, the circumstances of crimes committed by professional participants in the justice system have not yet been given thorough attention within the criminal law cycle. The purpose of this article is to clarify the peculiarities of the circumstances of criminal offenses committed by professional participants in the justice system in the field of justice. Based on the scientific research conducted, it has been established that the circumstances of their commission cover and reflect the geographical and spatial characteristics of the commission of criminal acts, preparation for their commission, and/or concealment (in the narrow sense). A typical feature of the circumstances of the commission of the criminal offenses under study is that the majority of them are committed in conditions of obviousness, i.e., in the presence of potential victims and witnesses, and only a few are committed in conditions of non-obviousness—secretly, without victims and witnesses, etc. Therefore, the prospects for further research lie in determining the characteristics of a typical trace pattern, which is reflected in the circumstances of the commission of crimes of the type under investigation.